PENGARUH MINAT BELAJAR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PERKALIAN SISWA KELAS IV MI TARBIYATUL BANIN JAMBU SEMAMPIR GRESIK - Laili Mauliddina; Arissona Dia Indah Sari (Jurnal Al-Fatih, 2022)
This research was conducted by fourth grade students of MI Tarbiyatul Banin, in Jambu Hamlet, Semampir Village, Cerme District, Gresik Regency, East Java Province. This study aims to analyze the influence of interest in learning on the ability to understand the mathematical concept of multiplication. This study uses quantitative methods with data collection techniques using tests and distributing questionnaires to students. After conducting the research, the researcher found that there was a significant effect between students' interest in learning and understanding of mathematical concepts. In the normality test, it was obtained that the concept understanding sig was 0.052 and learning interest was 0.200, so the data variables were normally distributed. In the homogeneity test, the sig value of 0.408> 0.05, it can be concluded that the variable understanding of mathematical concepts and the variable of interest in learning are homogeneous. So the researcher will use parametric test. In the correlation test, the data obtained from the variable interest in learning and the variable understanding of mathematical concepts have a relationship or correlation because the significant value is r table, 0.570 > 0.339 so that there is a significant influence between students' learning interest on understanding mathematical concepts of fourth grade students at MI Tarbiyatul Banin.